Differential Evolution in Hydrochemical Characteristics Amongst Porous, Fissured and Karst Aquifers in China - Chengsong Li; Jie Fang; Feisheng Feng; Tingting Yao; Yongping Shan; Wanli Su (Hydrology, 2025)
The efficacy of water resource management and protection hinges on a profound understanding of the controlling factors and regulatory mechanisms that shape groundwater chemistry within aquifers. Despite this, our comprehension of how groundwater chemistry and ion sources vary across diverse aquifer types remained limited. To bridge this gap, our study conducted a detailed hydrochemical and statistical investigation of porous, fissured, and karst aquifers. By applying multivariate statistical techniques, including principal component analysis (PCA) and hierarchical cluster analysis (HCA), the hydrochemical characteristics and main ion sources of each aquifer type, as well as distinct controlling factors and regulation patterns, were determined. Notably, evaporation predominantly affected the hydrochemistry of porous aquifers, whereas mineral dissolution and rock weathering processes played a pivotal role in shaping the groundwater evolution of fissured and karst aquifers. HCO3− and SO42− are the most common anions of all types, while Na+ is dominant in porous and fissured aquifers and Ca2+ is dominant in karst aquifers. The most common hydrochemical types identified were HCO3-Ca·Mg (accounting for approximately 56.84%) and SO4·Cl-Na (constituting approximately 21.75%). PCA results revealed that lateral recharge from fissured aquifers in hilly regions into the groundwater of porous aquifer, and wastewater discharge and agricultural fertilizer application, significantly impact the groundwater chemistry across all three aquifer types. It is worth noting that the dissolution of carbonate minerals, often influenced by human activities, had a profound effect on the hydrochemistry of each aquifer. Conversely, the dissolution of evaporitic minerals affected groundwater chemistry primarily through cation exchange processes. In summary, the hydrochemical characteristics of these aquifer types were predominantly shaped by a complex interplay of mineral dissolution, cation exchange, evaporation, and anthropogenic activities, with notable contributions from fissured aquifer recharge and pollution. These insights were critical for informing national-level strategies for groundwater resource protection and management.